Chlorogenic Acid Improves NAFLD by Regulating gut Microbiota and GLP-1 - Shi, Ameng; Li, Ting; Zheng, Ying; Song, Yahua; Wang, Haitao; Wang, Na; Dong, Lei; Shi, Haitao (Frontiers in Pharmacology, 2021)
Our previous studies have shown that chlorogenic acid (CGA) could significantly improve acute and chronic liver injury through antioxidant and anti-inflammatory activities. However, its effect on non-alcoholic fatty liver disease (NAFLD) are not entirely clear. This study aims to explore the effect of CGA on NAFLD and whether it regulates the gut microbiota and Glucagon-like peptide-1 ( GLP-1 ). NAFLD mice were established by high fat diet (HFD) and treated with or without CGA. Serum transaminase, fasting plasma glucose (FPG), blood lipids, insulin, GLP-1 and lipopolysaccharide (LPS) were detected. Liver histology was evaluated with HE staining. TLR4 signaling pathway was analyzed with western blot and inflammatory cytokines were detected with real-time PCR. The numbers of gut microbiota were determined with real-time PCR of the bacterial 16S rRNA gene. Expressions of intestine tight junctional protein were examined with immunohistochemistry. CGA could alleviate HFD-induced hepatic steatosis and inflammation, reduce serum transaminase, FPG and blood lipids, increase insulin sensitivity. CGA also could reverse HFD-induced activation of TLR4 signaling pathway and expression of TNF-α and IL-6 in liver. Meanwhile, CGA increased the abundance of Bifidobacterium and Lactobacillus and reduced the abundance of Escherichia coli and Enterococcus in feces. Furthermore, CGA could increase the expression of tight junction proteins Occludin and ZO-1 in intestinal tissue. Moreover, CGA could decrease the level of LPS and increased the level of GLP-1 in portal vein. These results indicate that CGA protects against HFD-induced hepatic steatosis and inflammation probably through its anti-inflammatory effects associated with changes of gut microbiota and an increase of GLP-1 secretion and thus can be used as a potential drug for the treatment of NAFLD.